Application of Benson’s Relaxation Technique to Reduce Blood Glucose Levels in Type II Diabetes Mellitus Patients: A Case Study in Sukoanyar Village, Pakis District - Louris Sam Pratama; Zaqqi Ubaidillah (Jurnal Kesehatan dan Kedokteran, 2025)
Type II Diabetes Mellitus (T2DM) is a chronic metabolic disorder with a high prevalence that often leads to complications and reduced quality of life. Management of T2DM requires not only pharmacological therapy but also complementary non-pharmacological interventions such as Benson’s relaxation technique, which may lower blood glucose levels through physiological and psychological mechanisms. This case study aimed to analyze the effectiveness of Benson’s relaxation in reducing blood glucose levels in an elderly patient with T2DM. The subject was a 70-year-old woman residing in Cokro Hamlet, Sukoanyar Village, Pakis District, Malang Regency. The intervention was conducted over three consecutive days, with each session lasting 20 minutes. Data were collected through interviews, observation, and measurement of random blood glucose (RBG) before and after each intervention. The results showed a gradual reduction in blood glucose levels, from 462 mg/dL (pre) to 440 mg/dL (post) on day one, 325 mg/dL to 301 mg/dL on day two, and 164 mg/dL to 146 mg/dL on day three. The patient also reported reduced fatigue, decreased tingling, improved sleep quality, and a greater sense of calm after undergoing the therapy. These findings indicate that Benson’s relaxation is a simple, safe, cost-effective, and feasible complementary intervention that can be practiced independently by patients and families at home, supporting holistic management of T2DM.